DESCRIPTION OF KNOWLEDGE LEVEL AND COMPLIANCE OF CALCIUM TABLET CONSUMPTION IN PREGNANT MOMS IN MIDWIFERY POLICLINIC RSD MANGUSADA BADUNG REGENCY - Ida Ayu Cendana Putri; I Gusti Agung Ari Widarti; Ni Made Yuni Gumala (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2020)
Pregnant women need more nutrients than when they are not pregnant. This is caused by nutrients that are consumed for the mother and fetus. Lack of calcium intake during pregnancy can affect growth in the fetus. The purpose of the study was to obtain an overview of the level of knowledge and compliance with consumption of calcium tablets in pregnant women at the Midwifery Polyclinic at RSD Mangusada, Badung Regency. The population in this study were pregnant women who had their gynecology checked in the obstetric clinic. The sample size obtained was 43 samples with the sampling method using a purposive sampling technique where the samples taken were pregnant women with the second and third trimesters. Data collected in May 2019 include primary data and secondary data with observational type and cross sectional design. In this study, the results of the knowledge of pregnant women regarding calcium with enough categories were 24 pregnant women (55.8%), less categories as many as 5 pregnant women (11.6%), and good categories as many as 14 pregnant women (32.6%). While obedient pregnant women consumed calcium tablets as many as 42 pregnant women (97.67%) and those who did not comply with calcium tablets as many as 1 pregnant women (2.33%). These results indicate that the level of knowledge of pregnant women about calcium is still in the less category with the number of 5 pregnant women (11.6%) caused by a lack of knowledge of pregnant women about calcium. Therefore, it is expected that health workers will provide information about the benefits of the importance of taking calcium tablets during pregnancy so that pregnant women are more aware and obedient in taking calcium tablets as recommended. Keywords: Knowledge Level, Compliance Level, Calcium Tablet